An emerging allergen: Cannabis sativa allergy in a climate of recent legalization - Bradley Jackson; Erica Cleto; Samira Jeimy (Allergy, Asthma & Clinical Immunology, 2020)
Abstract Considering its recent legalization in Canada, the health implications of Cannabis sativa exposure, including allergy, are coming to the forefront of medical study and interest. C. sativa allergy is an issue that affects recreational users of the substance, processors, agricultural workers, and contacts of Cannabis aeroallergens and secondhand product. Allergies to C. sativa are heterogenous and span the spectrum of hypersensitivity, from dermatitis to rhinoconjunctivitis to life-threatening anaphylaxis. Due to its recent legalization, sensitized individuals will have increasing exposure from direct contact to agricultural pollens. Diagnosis and treatment of Cannabis allergy are developing fields that are already showing promise in the identification of culprit antigens and the potential for immunotherapy; however, much responsibility still falls on clinical diagnosis and symptom management. Hopefully, given the current explosion of interest in and use of Cannabis, C. sativa allergy will continue to garner awareness and therapeutic strategies.